2018
DOI: 10.1111/1475-6773.13034
|View full text |Cite
|
Sign up to set email alerts
|

Dual Use and Hospital Admissions among Veterans Enrolled in the VA's Homeless Patient Aligned Care Team

Abstract: Objective To examine the association between reliance on VA outpatient care and hospital admissions among Medicare‐eligible Veterans enrolled in the Homeless Patient Aligned Care Team (H‐PACT). Data Sources/Study Setting Registry of H‐PACT enrollees linked to VA and Medicare utilization data for 2013. Study Design After assigning Veterans to two groups according to whether they received >90 percent of outpatient care in VA (higher reliance) or <90 percent of outpatient care in VA (lower reliance), generalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…(24) Trivedi and colleagues observed that Veterans enrollment in HPACTs with significant dual use of Medicare and VA outpatient care was strongly associated with acute hospitalizations financed by Medicare and high fragmentation of care. (25) Other studies showed mixed results. Patel provided an early case study in 2013 at the VA greater Los Angeles Healthcare System of 47 Veterans who were assigned to the West LA HPACT for at least six months without any statistically significant change in acute ED utilization after six months despite significant increases in HPACT visits and SW encounters.…”
Section: Resultsmentioning
confidence: 97%
“…(24) Trivedi and colleagues observed that Veterans enrollment in HPACTs with significant dual use of Medicare and VA outpatient care was strongly associated with acute hospitalizations financed by Medicare and high fragmentation of care. (25) Other studies showed mixed results. Patel provided an early case study in 2013 at the VA greater Los Angeles Healthcare System of 47 Veterans who were assigned to the West LA HPACT for at least six months without any statistically significant change in acute ED utilization after six months despite significant increases in HPACT visits and SW encounters.…”
Section: Resultsmentioning
confidence: 97%
“…, and Trivedi et al. ). One study focused on health care use in VA and VA community care (Rosen et al.…”
mentioning
confidence: 96%
“…Two studies linked Medicare data to examine the impact of the VA's patient aligned care team intervention (Trivedi et al. ; Reddy et al. ).…”
mentioning
confidence: 99%
See 2 more Smart Citations